Escape from the Phagosome: The Explanation for MHC-I Processing of Mycobacterial Antigens? - Harriff, Melanie; Purdy, Georgiana; Lewinsohn, David M. (Frontiers in Immunology, 2012)
Mycobacterium tuberculosis (Mtb) is thought to live in an altered phagosomal environment. In this setting, the mechanisms by which mycobacterial antigens access the major histocompatibility class I (MHC-I) processing machinery remain incompletely understood. There is evidence that Mtb antigens can be processed in both endocytic and cytosolic environments, with different mechanisms being proposed for how Mtb antigens can access the cytosol. Recently, electron microscopy was used to demonstrate that Mtb has the potential to escape the phagosome and reside in the cytosol. This was postulated as the primary mechanism by which Mtb antigens enter the MHC-I processing and presentation pathway. In this commentary, we will review data on the escape of Mtb from the cytosol and whether this escape is required for antigen presentation to CD8+ T cells.